The body as a medium of expression in the domain of geography - Brozović Rončević, Dunja; Škara, Danica (2005)
Cultures of all times and places have always been vitally concerned with the body. This study shows that human body is often used as a model to describe our natural and physical environment. The results of the cross-cultural analysis show that in different languages and cultures the body parts are often used to conceptualize place names and other geographical phenomena. The metaphorical use of the human body reveals that our perception of reality is inseparable from our embodiment. Parts of human body have become the measure of comprehension for the non-human world.
Podserija: Leksik i onomastika serije: Quaderni Internazionali di RION 1 / RION International Series 1 ; RION = Rivista Italiana di Onomastica, Rim
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG